The effect of family background and environmental factors on academic achievement of secondary school students in Saki West Local Government Area. (2009)
The study investigated the relationship between the role of family background and environment on academic is achievement of secondary school students. The study made use of the random sampling technique, which involved two thousand (2000) respondents consists of male and female students in selected secondary schools in urban and rural areas within Saki West Local Government Area of Oyo State. The correlational research design was adoptedfor the study. The research instrument used is the family backgro und and environment questionnaire. The method of data analysis used for the study is the multiple regression analysis. This was used in the study to establish the relationship between the independent and dependent variables of the study. Two research questions were tested using the data obtainedfrom the field. The research questions were tested at the 0.05 level of significance and the research findings indicated that the independent variables (Socioeconomic status, family size, school location, school environment, physical facilities and peer influence) were significant contributions to the prediction of the dependent variable (Academic Achievement). The results of the findings as well as the appropriate recommendations based on the findings were highlighted. Conclusion was drawn based on the outcome of the study.